Effects of Sulfamethoxazole on the Microbial Community Dynamics During the Anaerobic Digestion Process - Mazzurco Miritana, Valentina; Massini, Giulia; Visca, Andrea; Grenni, Paola; Patrolecco, Luisa; Spataro, Francesca; Rauseo, Jasmin; Garbini, Gian Luigi; Signorini, Antonella; Rosa, Silvia; Barra Caracciolo, Anna (Frontiers in Microbiology, 2020)
Anaerobic digestion (AD) treatment of cattle manure and slurry makes it possible to produce biogas, a renewable and storable biofuel, as well as digestate, a residual organic compost that can be used to replace chemical fertilizers. On the other hand, the intense use of antibiotics (e.g. sulfamethoxazole) in animal husbandry practices is showing increasing negative impacts, resulting from the release in agroecosystems of still metabolically active molecules. In the present study, cattle-manure was used as feedstock for AD experiments where some batches were spiked with 5 mg L-1 of sulfamethoxazole (SMX). Adding the antibiotic affected the microbial community dynamic; in particular, the efficiency of the acidogenic and acetogenic phases of the process corresponded to a higher CH4 and H2 production than in the Control. SMX was also degraded and at the end of the experiment (69 d) just 20% of its initial concentration was found. The relative abundance (ARG/16S) of resistance genes sul1, sul2 and the proxy intI1 initially found in the ingestate decreased during the AD both in the spiked and Control batches, suggesting that this process lowers the likelihood of ARGs spreading.